MANAQIB WRITING IN THE CIRCLE OF THE TARIQA QADIRIYYA WA NAQSYABANDIYYAH: A STUDY ON MUHAMMAD SIDDIQ AL-SALIHI’S NAYL AL-AMANI - Widiyanto, Asfa (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2015)
The manaqib of ?Abd al-Qadir al-Jilani is of particular importance in the circle of the Tariqa Qadiriyya wa Naqsyabandiyyah (TQN). Some leaders of the TQN have done their best to give a translation and explanation of this manaqib. For instance, Muhammad Siddiq al-Salihi composed a work titled Nayl al-am?n? f? dhikr manaqib al-qu?b al-rabb?n? sayyidin? al-shaykh ?Abd al-Q?dir al-J?lan?. Another leader, Muslih ibn ?Abd al-Rahman al-Maraqi, wrote a treatise titled al-N?r al-burh?n? f? tarjamat al-lujayn al-d?n? f? dhikr nubdhah min manaqib al-shaykh ?Abd al-Q?dir al-J?lan?. The TQN master Nawawi Siddiq al-Zarkashi wrote a treatise titled Fuyu??t al-rabb?n? f? kayf?y?t qir??at manaqib sul??n al-awliy?? al-shaykh mu?y? al-d?n ?Abd al-Q?dir al-J?lan?. This paper will pay particular attention to the Nayl al-amani, since this work is relatively unknown in Indonesian academia. This book is written in standard Arabic, something which is nowadays rare in the Pesantren and tariqa scholarship. This book is read during the monthly communal ritual of the TQN in the Pesantren Manba? al-Falah, Dawe, Kudus, Central Java. This paper strives to unravel the narratives of hagiography in Nayl al-amani and also highlight the uniqueness of Nayl al-amani, most particularly in comparison with the two manaqib writings in the circle of the TQN in Central Java.